Neurodermatitis in Baquba City, Diyala Governorate/Iraq Clinical and histopathological study - Khalil Ibrahim, Gibran; ,Yahya abbood , Sarmad; D Hameed, Saad (Diyala Journal of Medicine, 2023)
Background: Many patients that have itchy thickened skin lesions are lichenified, it's located on the extremities namely on the knees, feet, dorsum of the hands, and /or elbows was being seen bilaterally and may be symmetrically. Objective: To evaluate clinical and histopathological features of neurodermatitis with some similarities to psoriasis in Iraqi patients. Patients and Methods: Twenty- Five patients with neurodermatitis attending Department of Dermatology, Baquba Teaching Hospital were enrolled in this study in time between 1st January 2020 to 31th January 2021. All patients were being examined and full history was taken, including age of the patients, onset and duration of the disease, severity and type of itching. A full examination was done to identify the character, colour, shape, site, and involvement of other body site of lesion. Incisional biopsy specimens from both lesion and adjacent normal skin were obtained from 9 patients and submitted to histological assessment. Results: Ten of the patients (40%) were male and fifteen (60%) were females, their age ranged from 29-70 years, with a mean of 49.5 years. The average duration ranged from one month- 15 years with median 7.5 years. Clinically; patients have severe itchy plaques that distributed bilaterally like those of psoriasis, involvement of the knees (56%), dorsum of the both hands, feet, and elbows, also having ( lichenification ,that is characterized by thickening of the skin and exaggeration of the skin lines ) which characteristic of the individual lesion of lichen simplex chronicus, these plaques were symmetrical, well defined, sharper, more keratotic, violaceous pigmentation, marked accentuation and thickening of skin. Psoriatic scales are not present typically on the plaques of these patients. These plaques mainly located on extremities. Nine specimens' taken for histopathologiacl findings showed hyperkeratosis, acanthosis, dermal papilomatosis, suprapapillary epidermal thinning. All patients mentioned a severe itching which was paroxysmal in typing, more severe in the evening. Conclusion: ( Lichenified psoriasis) Psoriatic neurodermatitis might be lichen simplex chronicus as a result to repetitive itching and scratching of plaque psoriasis. This was typical neurodermatitis and not psoriasis.